LITERATURE REVIEW: DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP KESEHATAN MENTAL REMAJA - Haqila Khairunnisa,; Fitria Nanda,; Debie Anggraini, (Nusantara Hasana Journal, 2024)
Due to its ability to transfer all actions online, mobile phones have become an essential tool for everyone. More than 2,000 teens access social media via their phones, 92% of the time, according to a 2015 survey. Physical and mental illnesses of teens including obesity, changes in sleep patterns, dangerous lifestyles (drugs and alcohol), and increased stress are some of the main impacts from social media. Therefore, in utilizing social media on a daily basis, time management is very important. Finding the relationship between teenagers' social media use and their physical and mental health was the goal of this study. In this research, researchers used a systematic observation method, where articles were selected using the PRISMA method. The articles used were obtained from online database facilities via the Google Scholar and ScienceDirect pages. The articles obtained were selected based on publications published from 2020 to 2023 (3 years). Of the eight selected articles, the results show that all articles state that there is a relationship between the use of social media and the mental and physical health of teenagers. Therefore, it can be concluded that the better teenagers manage their time in using social media every day, the lower the incidents that affect teenagers' mental and physical health.